Community Mobilization Led by Lay Actor, a Directed Participation in Tax Culture - Utomo, Rachmad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
Community leaders indeed become strategic actors for the government. In Pondok Aren, a meatball seller has led the UMKM Sahabat Pajak (USP) or micro, small, and medium enterprises (SME) community tax-friendly, they were successfully directed to mobilize a social movement